(untitled) (Research, Society and Development, 2019)
The evaluation of the educational performance of youngsters and adults can occur through the National Exam for Certification of Competences of Youngsters and Adults. The tests that comprise the exam have among the purposes, to be evaluation instruments to manage the quality of education focused on the modality of Youth and Adult Education, assessing the skills and abilities foreseen in each test, as well as assessing the learning resulting from curricular components common to education such as Mathematics. The objective of this study is to analyze the performance of participants of the National Exam for Certification of Competences of Youngsters and Adults, Lower Secondary Education, in the Mathematics test of the year 2014. The research is of quantitative approach. The microdata available from the National Institute for Educational Studies and Research "Anísio Teixeira" (Inep) were used. For the analysis of the data was used descriptive statistics and the SPSS Software (Statistical Package for the Social Sciences). The results showed that males obtained better means in mathematics than females; As for location, the urban area presented a higher average than the rural area, indigenous community and quilombola community; already compared to the Brazilian region, the participants of the Southeast Region showed a better average in the component than in the South, Central West, North and Northeast regions. We suggest studies that re-analyze if the competences related to Mathematics are being reached, and how socioeconomic factors can interfere when related to the variables analyzed in this study. It is also suggested to use more sophisticated statistical tests for data analysis.